2018
DOI: 10.1111/odi.13003
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of proteins of the NLRP3 inflammasome in patients with periodontitis and uncontrolled type 2 diabetes

Abstract: Objectives To evaluate the expression of proteins related to activation of the NLRP3 inflammasome in patients with chronic periodontitis (CP) and type 2 diabetes mellitus (T2D), and to determine whether the exacerbated periodontal pathological process observed in diabetic patients is related to its upregulation. Materials and Methods We performed an observational, analytical, cross‐sectional study in three study groups: individuals systemically and orally healthy, and patients with CP with and without T2D. Gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 28 publications
4
45
0
Order By: Relevance
“…Although an upregulation of caspase‐1 in response to periodontal bacterial challenge , , , , was reported, others noted no changes or a decrease in its levels in in vitro studies. Clinical data has shown that caspase‐1 was higher in the gingiva of CP patients compared with healthy controls , , ; however, similar caspase‐1 levels were reported in the saliva of CP and AgP patients, and periodontally healthy groups . The current study also identified no differences in caspase‐1 levels between the CP, AgP, and G groups compared with the H group, although a tendency toward increased levels were seen in the disease groups ( P > 0.05) (Fig.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although an upregulation of caspase‐1 in response to periodontal bacterial challenge , , , , was reported, others noted no changes or a decrease in its levels in in vitro studies. Clinical data has shown that caspase‐1 was higher in the gingiva of CP patients compared with healthy controls , , ; however, similar caspase‐1 levels were reported in the saliva of CP and AgP patients, and periodontally healthy groups . The current study also identified no differences in caspase‐1 levels between the CP, AgP, and G groups compared with the H group, although a tendency toward increased levels were seen in the disease groups ( P > 0.05) (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Another inflammasome component, ASC, has been reported as upregulated, downregulated and unaffected in response to periodontal pathogens in different cell types. Clinical results have shown that ASC expression is higher in the saliva and gingiva of periodontally diseased patients. In contrast, in the current study no differences were detected in ASC levels between any of the disease and control groups ( P > 0.05) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, the generation of reactive oxygen species (ROS) in response to LPS is the key signaling event in the pro-inflammatory response in HGFs, 11 and the ROS can also stimulate the activation of NLRP3 inflammasomes, which can further promote periodontitis. 12 The expression of NLRP3 inflammasomes is upregulated in periodontitis, 13 and the inhibition of the NLRP3 inflammasome can reduce the periodontitis in mice. 14 Thus, inhibition of NLRP3 inflammasome activation and the resulting pyroptosis may be essential in improving periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…The NLRP3 mutated allele (C) is a variant in the intron 7 of chromosome 1q44 and was previously correlated to the higher transcriptional activity of the gene when compared to the wild T allele [61]. An over expression of the NLRP3 inflammasome and a downregulation of NLRP3 inhibitors were observed in the gingival tissue of patients with PD [28,31,39]. The NLRP3 activation depends on signals provided by recognition of PAMPs, such as microbial lipopolysaccharides (LPS), and DAMPs (ie.…”
Section: Discussionmentioning
confidence: 99%
“…Several inflammasomes have been described: NLR family pyrin domain-containing 1 (NLRP1), NLRP2, NLRP3, NLR family CARD domain-containing 4 (NLRC4) and AIM2 [27]. NLRP3 is the better characterized member and shown to be involved in the innate immune reaction of infectious, inflammatory and chronic diseases [28,29]. Overexpression of NLRP3 in the gingival tissue and increased salivary levels of NLRP3 were observed in PD patients [30].…”
Section: Introductionmentioning
confidence: 99%